Optical Technologies for Endoscopic Real-Time Histologic Assessment of Colorectal Polyps: A Meta-Analysis. (August 2019) - Mason, Sam E.; Poynter, Liam; Takats, Zoltan; Darzi, Ara; Kinross, James M.
Abstract : OBJECTIVES: Accurate, real-time, endoscopic risk stratification of colorectal polyps would improve decision-making and optimize clinical efficiency. Technologies to manipulate endoscopic optical outputs can be used to predict polyp histology in vivo ; however, it remains unclear how accuracy has progressed and whether it is sufficient for routine clinical implementation. METHODS: A meta-analysis was conducted by searching MEDLINE, Embase, and the Cochrane Library. Studies were included if they prospectively deployed an endoscopic optical technology for real-time in vivo prediction of adenomatous colorectal polyps. Polyposis and inflammatory bowel diseases were excluded. Bayesian bivariate meta-analysis was performed, presenting 95% confidence intervals (CI). RESULTS: One hundred two studies using optical technologies on 33, 123 colorectal polyps were included. Digital chromoendoscopy differentiated neoplasia (adenoma and adenocarcinoma) from benign polyps with sensitivity of 92.2% (90.6%–93.9% CI) and specificity of 84.0% (81.5%–86.3% CI), with no difference between constituent technologies (narrow-band imaging, Fuji intelligent Chromo Endoscopy, iSCAN) or with only diminutive polyps. Dye chromoendoscopy had sensitivity of 92.7% (90.1%–94.9% CI) and specificity of 86.6% (82.9%–89.9% CI), similarly unchanged for diminutive polyps. Spectral analysis of autofluorescence had sensitivity of 94.4% (84.0%–99.1% CI) and specificity of 50.9% (13.2%–88.8% CI). Endomicroscopy had sensitivity of 93.6% (85.3%–98.3% CI) and specificity of 92.5% (81.8%–98.1% CI). Computer-aided diagnosis had sensitivity of 88.9% (74.2%–96.7% CI) and specificity of 80.4% (52.6%–95.7% CI). Prediction confidence and endoscopist experience alone did not significantly improve any technology. The only subgroup to demonstrate a negative predictive value for adenoma above 90% was digital chromoendoscopy, making high confidence predictions of diminutive recto-sigmoid polyps. Chronologic meta-analyses show a falling negative predictive value over time. A significant publication bias exists. DISCUSSION: This novel approach to meta-analysis demonstrates that existing optical technologies are increasingly unlikely to allow safe "resect and discard" strategies and that step-change innovation may be required. A "diagnose and leave" strategy may be supported for diminutive recto-sigmoid polyps diagnosed with high confidence; however, limitations exist in the evidence base for this cohort.